KOMPOSISI UNSUR DAN KARAKTERISTIK MINERAL PASIR PUYA DARI SINTANG, KALIMANTAN BARAT (ELEMENT COMPOSITION AND MINERAL CHARACTERISTIC OF PUYA SAND FROM SINTANG, WEST KALIMANTAN) - Duwan Agustina; Risa Nofiani; Imelda H Silalahi (Indonesian Journal of Pure and Applied Chemistry, 2021)
Puya sand is a byproduct from local gold mining activities found in Sintang, West Kalimantan. Puya sand is usually left by the miners after the mining activity leaving a pile of abandoned sands. Mineral characterisation conducted by using XRD and XRF methods demonstrated that the sand contains valuable elements and mineral, i.e. zircon silicate, quartz and ilmenite. A simple physical flotation separation method removed quartz remaining material containing concentrated zircon silicate. XRD analysis by using Search-Match followed by amount calculation by using Rietveld refinement showed that the sand consists of zircon silicate (58.3%), ilmenite (35.2%) and anatase (6.5%). Elemental analysis by using XRF presented the percentage of Zr, Ti, Fe and Si is 41.0, 23.9, 13.06 and 8.3, respectively. Hafnium with 1.5% was also observed along with Th, U and rare earth elements (REEs), such as Nd, Y, Eu, and Yb.